La “mayoría” mudéjar en León y Castilla: legislación real y distribución de la población (Siglos XI-XIII) - Echevarría, Ana (En la España Medieval, 2006)
The origins of “Mudejarismo” in the kingdom of Leon-Castile after Alfonso VI have been obviated by scholars, who have preferred to focus on the more abundant sources dealing with 14th and 15th century Muslims in Castile. This paper will focus on the three groups of Muslims considered by royal legal codes: free Muslims, later known as Mudejars; Muslim slave workers or captives, and Muslim converts. The changes in status of Muslims conquered at the time, which contributed to create the flourishing Castilian aljamas of the Late Middle Ages, are revealed in royal law codes and records from Spanish archives.